Marques d'oralitat en els xats - Torres i Vilatarsana, Marta (Caplletra. Revista Internacional de Filologia, 2008)
The aim of this article is to determine, from the analysis of a real corpus, whether the traits associated with colloquial orality are present in chats. Chats, from the channel’s point of view, belong to the written mood of production, which has traditionally been associated with a high level of formality. However, they presentfeatures which are characteristic of the oral discourse, as Torres and Cuenca (2007) state. We have chosen as corpus of analysis chats which present a low level of formality and which are considered to be representative of the model of language used there. The challenge is focused on revealing how aspects of colloquial orality are present in written texts. The article aims at breaking with some topics associated to chat language: although formal transgression is evident, the level of grammatical respect is similar to colloquial oral discourse.